Adsorptive removal of bisphenol A from aqueous solutions using phosphonated levan - HACIOSMANOĞLU, GÜL GÜLENAY; GENÇ, SEVAL; CAN, ZEHRA SEMRA (ELSEVIER, 2019)
In this study, the potential use of phosphonated Halomonas Levan (PhHL) as a natural and cost effective adsorbent for Bisphenol A (BPA), was systematically investigated via the study of the adsorption equilibrium, kinetics, and reuse potential as well as the interpretation of adsorption mechanism. The effects of pH and temperature on the adsorption were also evaluated. The maximum amount of BPA adsorbed on the unit weight of PhHL was determined as 104.8 (-/+ 5.02) mg/g (at 298 K) and the maximum adsorption capacity was calculated as 126.6 mg/g by Sips model. FTIR and XPS studies were conducted to elucidate the adsorption mechanism. Based on the obtained results OH-pi and CH-pi interactions were found to be effective in the adsorption mechanism. The reuse ability was studied with three cycles of adsorption-desorption, and the results showed that the BPA adsorbed per gram of the PhHL decreased 28.6% after the third cycle. This study has shown that PhHL can be used as an effective adsorbent for the removal of BPA from aqueous solutions. The obtained results may be useful in the development of PhHL based adsorption systems for the removal of EDCs with similar chemical properties to BPA.
Keywords: Endocrine disrupting compounds; Bisphenol A; Adsorption; Phosphonated levan; Pi interactions; LINKED BETA-CYCLODEXTRIN; CH-PI-INTERACTION; WATER; SURFACE; ADSORBENT; NANOCOMPOSITE; COMPOSITES; POLYMER; MODEL